Museum Management of Learning Spaces in National Civilisations: Synthesis of Asian Civilisations Museum, Republic of Singapore and National Palace Museum, Republic of China - Kamput, Kedchapan (Thai Journal of East Asian Studies, 2019)
This research paper sets out to assess the strategic management of museums; and learning of historical legacies, cultural heritage and national civilisations. The studies were conducted in two museums, namely, Asian Civilisations Museum, Republic of Singapore and National Palace Museum, Republic of China. The research used qualitative method and was based on the concepts of museum sociology and museum management. It has been found that (1) Asian Civilisations Museum was established for Singaporean nationality, aiming at enhancing multiracial and multicultural society. The development of National Palace Museum was based on historical legacies as the Chinese revolution has finally led to the political predisposition and cultural politics which aim at promoting Taiwannese consciousness, cultural diplomacy and Taiwan’s nation-branding process; (2) There has been a synthesis of museum management strategies for learning about civilisations through the integration of knowledge in the following areas; fine arts, history and anthropology. Content area was portrayed using chronological displays about religious arts which reflect the roots of ancient Asian civilisations from ancient national history to national history through ancestral cultural heritages at the geographical location of emporium and cultural crossroads of foreigners and indigenous peoples to richness of Pan-Asian civilisation. Under the new regionalism in the context of globalisation, the mission statement of civilisation museums were based on the reinforcement of civilisation consciousness for global citizens who share the heritage of mankind.